1993
DOI: 10.1006/dbio.1993.1007
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-Stimulating Hormone Induction of Steel Factor (SLF) mRNA in Mouse Sertoli Cells and Stimulation of DNA Synthesis in Spermatogonia by Soluble SLF

Abstract: Follicle-stimulating hormone (FSH) and its intracellular mediator, cAMP, increase the mRNA levels for the Steel factor (SLF, the c-kit ligand) in cultured primary mouse Sertoli cells. The inductive effect of cAMP is more evident in cultures from 13-day-old animals than in cultures from 18-day-old animals. Analysis through the polymerase chain reaction (PCR) indicates that (Bu)2cAMP or FSH treatment increases the levels of the mRNAs for both the potentially soluble form and the transmembrane form of SLF in cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
157
0
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(164 citation statements)
references
References 0 publications
3
157
0
4
Order By: Relevance
“…However, kit is known to play important roles also during post-natal stages of spermatogenesis (Sette et al, 2000). In the adult testis, the kit receptor is expressed in differentiating spermatogonia, but not in spermatogonial stem cells, whereas KL is expressed by Sertoli cells under FSH stimulation in both a soluble and a transmembrane form, which are generated by alternative splicing (Rossi et al, 1993). The soluble form of KL stimulates DNA synthesis in type A spermatogonia cultured in vitro, and injection of anti-kit antibodies blocks their proliferation in vivo (Rossi et al, 1993;Packer et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, kit is known to play important roles also during post-natal stages of spermatogenesis (Sette et al, 2000). In the adult testis, the kit receptor is expressed in differentiating spermatogonia, but not in spermatogonial stem cells, whereas KL is expressed by Sertoli cells under FSH stimulation in both a soluble and a transmembrane form, which are generated by alternative splicing (Rossi et al, 1993). The soluble form of KL stimulates DNA synthesis in type A spermatogonia cultured in vitro, and injection of anti-kit antibodies blocks their proliferation in vivo (Rossi et al, 1993;Packer et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…In the adult testis, the kit receptor is expressed in differentiating spermatogonia, but not in spermatogonial stem cells, whereas KL is expressed by Sertoli cells under FSH stimulation in both a soluble and a transmembrane form, which are generated by alternative splicing (Rossi et al, 1993). The soluble form of KL stimulates DNA synthesis in type A spermatogonia cultured in vitro, and injection of anti-kit antibodies blocks their proliferation in vivo (Rossi et al, 1993;Packer et al, 1995). A point mutation in the kit gene, which impairs KL-mediated activation of phosphatydilinositol 3-kinase, does not cause any significant reduction in PGCs number during embryonic development, nor in spermatogonial stem cell populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to reliably assess the effect of exogenous growth factors on the proliferation of mouse SSCs, serum-free culture conditions were employed. It was reported that the addition of one to two growth factors could maintain cell survival in vitro (Rossi et al 1993). In our study, GDNF or LIF alone or in combinaion were supplemented to the medium and the effects on the mouse SSCs proliferation were evaluated.…”
Section: Discussionmentioning
confidence: 99%